SIFAT PAPAN WOL KAYU DARI KAYU SENGON DAN KAYU KARET PADA BEBERAPA MACAM UMUR - l M Sulastiningsih; Adi Santoso; Paribotro Sutigno (Jurnal Penelitian Hasil Hutan, 1995)
The  results  of  laboratory  test   of  wood-wool  board properties  made from  rubberwood (Hevea   brasiliensis)    and sengon  (Paraserianthes   falcataria)    are  reported  in this paper.   The wood used were obtained feom  different age groups i.e. 10  and 20 years for rubberwood and 5,  10  and  15  years for  sengon.  The properties  tested  were  board density,  moisture   content, thickness  reduction  due  to compression and bending strength.The physical  and mechanical properties  of sengon  wood-wool board which the  wood-wool was soaked  in  cold  water for  24 hours prior  to  board fabrication  were improved.  However, that treatment  did not improve the properties  of rubberwood wood-wool board.   The properties of wood-wool board made from different age groups of tree seem to be similar.